Validação do diagnóstico de enfermagem ‘Controle Emocional Instável’ no trauma cranioencefálico - Santos, Ana Carla Ferreira Silva dos (2017)
The consequences resulting from Traumatic brain injury (TBI) cause disabilities or physical disabilities (motor, visual, among others), cognitive (memory, attention, learning, among others) and or behavioral/emotional (loss of self-confidence, depression, anxiety, difficulty of Self-Control, irritability, aggression, among others) that can be temporary or permanent. The study aimed to perform the validation of content and clinical aspects of nursing diagnosis of ""Labile emotional control" in treated TBI outpatients. Methodological and descriptive study that used the model of Fehring for validation. The research was developed in two steps: Content validation and clinical validation. In the former, there was the participation of 31 experts to evaluate, by means of electronic questionnaire, the taxonomic structure of NANDA International concerning the diagnosis "Labile emotional control". The later was performed in the outpatient clinic of the University Hospital of the Federal University of Sergipe, between the months of August and September 2016 with a sample consisting of 40 patients in two distinct groups with mild TBI (n=20) and moderate TBI (n=20). For comparison of proportions among groups the z test (two groups) was used and with Bonferroni correction (3 groups). The results showed that the majority of experts considered the domain 05 (perception/cognition), Class 4 (cognition) and the wording (Labile emotional control) suitable for diagnosis, although they suggested modifications in the current definition of diagnosis Two of the defining characteristics were considered major (removal of the social situation and the expression of incoherent emotions with the triggering factor) and 11 secondary (removal of the professional situation, lack of contact with the eyes, crying without excessive feel sorrow, uncontrollable crying, involuntary crying, difficulty using facial expressions, embarrassment on the expression of emotions, tears, laughter in excess without feeling happiness, uncontrollable laughter and involuntary laughter. The total score of the diagnosis “Labile emotional control” was 0.69, considered valid. In the clinical validation, the characteristics that are considered important for the mild TBI were: professional situation leave, avoidance of social situation, embarrassment on the expression of emotions, expression of emotions would be inconsistent with the triggering factor and the secondary were absence of eye contact, excessive crying without feeling sadness, uncontrollable crying , involuntary crying, difficulty using facial expressions and tears and the irrelevant ones were laughter in excess without feeling happiness, uncontrollable laughters and involuntary laughter. In the moderate TBI group the following were identified as main characteristics: professional situation leaves, avoidance of social situation, excessive crying without feeling sadness, embarrassment on the expression of emotions, expression of emotions would be inconsistent with the triggering factor and the secondary were absence of eye contact, uncontrollable crying, involuntary crying, difficulty using facial expressions, tears, uncontrollable laughter and involuntary laughter. The total score was similar in both groups, 0.74, considered to be validated for the NANDA Taxonomy-I. It is concluded that almost all of the defining characteristics were considered valid for the diagnosis "Labile Emotional Control" in TBI.